Packaging material and manufacturing method of the same
Patent Information
- Application Number
- JP2024139184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0019】 本発明により、リリース性、ヒートシール性及び耐突き刺し性が良好な包装材を提供する。更には、耐水摩擦性、耐熱性、及び耐折り曲げ性に優れた包装材を提供することが可能となった。
Smart Images

Figure 2025036207000001 
Figure 2025036207000002 
Figure 2025036207000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging material and a method for producing the same. [Background technology]
[0002] In recent years, it has become common for product packages and other wrapping materials to be printed for decoration and surface protection. Furthermore, the quality of printing, such as the design, beauty, and luxury of the printed matter, can stimulate consumer purchasing motivation, and is therefore of great industrial value.
[0003] Generally, plastic films are mainly used to construct packages, and laminated packaging materials are often used in particular. For example, Patent Document 1 describes an invention of a laminated packaging material consisting of a base material, a printing layer, an adhesive layer, and a sealant layer, in which biomass resin is used in the printing layer and the adhesive layer. However, laminated packaging materials originally use a large amount of plastic film made of petroleum-derived materials. Therefore, there is a demand for paper-based packaging materials that are environmentally friendly, carbon neutral, and can further reduce the amount of plastic used, and technological developments are being made.
[0004] For example, as an example of using a paper substrate as part of a packaging material, Patent Document 2 describes an invention relating to a paper laminate having, in order, a resin layer, a print layer, a paper substrate layer, a metal deposition film layer, a gas barrier coating layer, and a heat-sealable resin layer. However, the resin layer is formed of low-density polyethylene or the like with a low glass transition temperature in order to provide heat sealability, and the toughness of the coating is insufficient, leaving problems with the releasability and heat resistance of the packaging material.
[0005] For example, Patent Document 3 describes an invention relating to a packaging material having a surface protective layer, a printing layer, a paper substrate layer, and a resin layer in that order, and the surface protective layer contains nitrocellulose. However, since the surface protective layer is formed only from nitrocellulose, it lacks water resistance and toughness, and therefore there are problems with the releasability and puncture resistance of the packaging material.
[0006] Therefore, packaging materials that do not use a large amount of plastic, such as laminate packaging materials, are desired, and for example, packaging materials using a paper base material are desired, but a satisfactory packaging material with excellent releasability and puncture resistance has not yet been found. Therefore, in order to impart practicality to packaging materials using a paper base material, in addition to solving the above problems, it is necessary to improve the water friction resistance, heat resistance, heat sealability, and folding resistance required of packaging materials. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-051796 A [Patent Document 2] JP 2006-256198 A [Patent Document 3] JP 2020-55171 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a packaging material having good releasability, heat sealability and puncture resistance, and further has an object to provide a packaging material having excellent water, friction and heat resistance. [Means for solving the problem]
[0009] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by using the packaging material described below, and have thus completed the present invention.
[0010] That is, the present invention provides a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the surface protective layer comprises a styrene-acrylic copolymer resin (A), The printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the surface protective layer has a 60 degree gloss value of 5 to 45 as measured by the method described in JIS Z 8741:1997; The average basis weight of the paper base material is 55 to 300 g / m 2 This relates to packaging materials.
[0011] That is, the present invention further relates to the packaging material as described above, which further comprises a barrier layer.
[0012] That is, the present invention relates to the packaging material, which further comprises an anchor coat layer on the paper base material.
[0013] That is, the present invention relates to the packaging material, wherein the surface protective layer has a 60 degree gloss value of 10 to 35, as measured by the method described in JIS Z8741:1997.
[0014] That is, the present invention relates to the packaging material, wherein the heat seal layer has a thickness of 1 to 10 μm.
[0015] That is, the present invention relates to the packaging material, wherein the heat seal layer contains an ethylene-vinyl acetate copolymer resin.
[0016] That is, the present invention relates to the packaging material, which is used as a secondary packaging material.
[0017] That is, the present invention relates to a packaging bag formed from the packaging material.
[0018] That is, the present invention provides a method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, comprising: The average basis weight of the paper base material is 55 to 300 g / m 2 and A step 1 of forming the printing layer by flexographically printing a printing ink containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin on one surface of the paper base material; A step 2 of forming the surface protective layer having a 60 degree gloss value of 5 to 45 as measured by the method described in JIS Z8741:1997 by flexographically printing an overcoat agent containing a styrene-acrylic copolymer resin (A) on the printed layer; and a step 3 of applying a heat seal agent to the other surface of the paper base material to form the heat seal layer. Effect of the Invention
[0019] The present invention provides a packaging material having good releasability, heat sealability and puncture resistance, as well as excellent water resistance, abrasion resistance, heat resistance and folding resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The following describes in detail the embodiments of the present invention. However, the following description of the components is merely an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.
[0021] In the following description, unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass." In addition, the packaging material may be abbreviated simply as "laminate," but this has the same meaning. In the following description of the present invention, "printing ink" refers to ink containing pigments and other colorants for forming a printed layer, and "overcoat agent" refers to a coating agent for forming a surface protective layer that does not contain pigments or other colorants, but does not exclude traces of colorants that have been unintentionally mixed in.
[0022] [Packaging material] The present invention relates to a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, wherein the surface protective layer contains a styrene-acrylic copolymer resin (A), the printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, The surface protective layer has a 60 degree gloss value of 5 to 45 as measured by the method described in JIS Z 8741:1997, and the paper base has an average basis weight of 55 to 300 g / m 2 The present invention relates to a packaging material having the above-mentioned structure, which has excellent releasability, heat sealability, puncture resistance, water abrasion resistance, and heat resistance. In the present invention, the surface protective layer contains a styrene-acrylic copolymer resin (A), which improves heat resistance, puncture resistance, and folding resistance. Furthermore, the packaging material of the present invention has a printing layer containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, and a surface protective layer containing a styrene-acrylic copolymer resin (A), which makes it possible to control the amount of light penetrating into the entire packaging material, and to achieve the above gloss value. The combination of the surface protective layer, printing layer, and paper substrate having the above-mentioned characteristics improves the film-forming properties of the printing layer and the surface protective layer, and furthermore, the surface protective layer has a gloss value at 60°C within the above-mentioned range, which makes the packaging material particularly excellent in water abrasion resistance and folding resistance. In addition, the packaging material of the present invention may further contain a barrier layer, and may contain an adhesive resin layer for bonding the barrier layer and the paper substrate layer. In addition, an anchor coat layer may be included on the paper substrate instead of the barrier layer.
[0023] The use of the packaging material of the present invention is not particularly limited, but it is preferably used as a secondary packaging material.
[0024] Suitable examples of the layered structure of the packaging material are as follows: In the following examples, " / " indicates the boundary between layers. Heat seal layer / paper base layer / printing layer / surface protection layer Heat seal layer / barrier layer / paper base layer / printing layer / surface protection layer Heat seal layer / paper base layer / barrier layer / printing layer / surface protection layer Heat seal layer / paper base layer / printing layer / barrier layer / surface protection layer Heat seal layer / anchor coat layer / paper base layer / printing layer / surface protection layer
[0025] [Surface protection layer] The surface protective layer contains a styrene-acrylic copolymer resin (A). When the surface protective layer contains the styrene-acrylic copolymer resin (A) of the present invention, the packaging material has good water friction resistance, heat resistance, releasability, puncture resistance, and folding resistance. In the surface protective layer, the content of the styrene-acrylic copolymer resin (A) is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the surface protective layer. When the content of the styrene-acrylic copolymer resin (A) is within the above range, the toughness of the surface protective layer is increased, and the heat resistance, puncture resistance, and folding resistance of the packaging material are improved. In addition, the thickness of the surface protective layer is preferably 0.3 to 10 μm, more preferably 1 to 7 μm, and even more preferably 3 to 5 μm.
[0026] The gloss value of the surface protective layer is 5 to 45, preferably 10 to 40, more preferably 10 to 35, further preferably 10 to 30, and particularly preferably 10 to 20. When the gloss value of the surface protective layer is within the above range, water friction resistance and folding resistance tend to be improved. The above gloss value is a 60 degree gloss value (Gs(60)) measured in accordance with JIS Z 8741:1997. The gloss value is different from the gloss (mirror reflection) of a metal layer such as an aluminum vapor deposition layer on the inside of a packaging material.
[0027] <Styrene-acrylic copolymer resin (A) contained in surface protective layer> The styrene-acrylic copolymer resin (A) is preferably an aqueous resin, which may be either a water-soluble resin or an aqueous emulsion resin, but is preferably an aqueous emulsion resin.
[0028] The styrene-acrylic copolymer resin (A) can be obtained by copolymerizing an acrylic monomer and a styrene monomer by a known method, and examples of the constituent styrene monomer include styrene, α-methylstyrene, β-methylstyrene, etc. These may be used alone or in combination of two or more. Among these, the styrene monomer preferably contains α-methylstyrene.
[0029] Suitable examples of the acrylic monomer include acrylic acid esters, methacrylic acid esters, etc. For example, examples of the acrylic acid esters include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate, and examples of the methacrylic acid esters include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. Also usable are carboxylic acid-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, and the anhydrides and half esters thereof. These may be used alone or in combination of two or more.
[0030] The styrene-acrylic copolymer resin (A) preferably has an acidic group, and in that case, the acid value is preferably 20 to 200 mgKOH / g, more preferably 30 to 150 mgKOH / g, and further preferably 80 to 120 mgKOH / g. When the styrene-acrylic copolymer resin (A) has an acidic group and the acid value is within the above range, the releasability and heat resistance of the packaging material are good.
[0031] The weight average molecular weight of the styrene-acrylic copolymer resin (A) is preferably from 2,000 to 600,000, more preferably from 50,000 to 600,000, and particularly preferably from 70,000 to 600,000.
[0032] The glass transition temperature of the styrene-acrylic copolymer resin (A) is preferably from -20 to 80°C, more preferably from -10 to 60°C, and further preferably from 0 to 40°C.
[0033] When the weight average molecular weight and glass transition temperature of the styrene-acrylic copolymer resin (A) are within the above ranges, the surface protective layer can have both toughness and flexibility, resulting in good releasability, puncture resistance, and bending resistance.
[0034] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acidic groups contained in 1 g of resin solid content, and is measured in accordance with JIS K0070.
[0035] The weight average molecular weight (Mw) can be measured, for example, by GPC (gel permeation chromatography), and can be calculated as a molecular weight converted using polyethylene glycol as a standard substance. The measuring device can be a GPC device such as Shodex GPC-401 manufactured by Showa Denko K.K., and the column can be a Shodex OHpak LB-805 manufactured by Showa Denko K.K., and the detector can be an RI (differential refractometer), and the measurement temperature is preferably a column temperature of 20 to 50°C. The eluent can be an aqueous solution of 0.1N NaNO3, and the flow rate is generally 0.2 to 5.0 mL / min.
[0036] The glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC measuring device, Shimadzu Corporation's "DSC-60A"), and the temperature of the inflection point in the baseline shift can be used as the glass transition temperature. The measurement is preferably performed in a nitrogen atmosphere, with the measurement temperature range being -100 to 200°C and the heating rate being 1 to 5°C / min.
[0037] The content of the structure derived from a styrene monomer in 100% by mass of the surface protective layer is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20 to 70% by mass.
[0038] <Other resins contained in the surface protective layer> The surface protective layer may further contain other resins. Examples of other resins include urethane resins, polylactic acid resins, polyamide resins, vinyl chloride-acrylic copolymer resins, castor oil resins, rosin resins, vinyl acetate resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, urethane-acrylic resins, styrene-allyl alcohol copolymer resins, styrene-maleic acid copolymer resins, rosin-modified maleic acid resins, dammar resins, and modified resins thereof. These resins can be used alone or in combination of two or more.
[0039] The styrene-acrylic copolymer resin (A) contained in the surface protective layer may be a commercially available product, for example, Joncryl 74J, Joncryl 537E, etc., manufactured by BASF.
[0040] <Additives contained in the surface protective layer> The surface protective layer of the present invention may contain various additives as required, such as dispersants, waxes, extender pigments, leveling agents, defoamers, film-forming assistants, water repellents, and release agents (silicone). Specifically, various additives can be added, such as dispersions of wax resin particles such as polyethylene wax to improve abrasion resistance; extender pigments such as silica, barium sulfate, resin beads, calcium carbonate, and talc to improve drying properties and coating film hiding properties; inorganic particles and adhesive resins (acrylic resin, vinyl acetate resin) to impart anti-slip properties; leveling agents to improve leveling properties; antifoaming agents to impart antifoaming properties; basic compounds such as sodium hydroxide and potassium hydroxide to impart re-solubility; and film-forming aids.
[0041] <Overcoat agent> The surface protective layer is preferably formed by an overcoat agent. The overcoat agent is preferably an aqueous overcoat agent. The overcoat agent preferably contains a styrene-acrylic copolymer resin (A) and an aqueous medium, and may further contain resins and additives other than the styrene-acrylic copolymer resin (A).
[0042] The solid content of the styrene-acrylic copolymer resin (A) in the overcoat agent is preferably 25 to 100 mass %, more preferably 25 to 75 mass %, and particularly preferably 25 to 45 mass %, of the total mass of the overcoat agent.
[0043] (aqueous medium) The overcoat agent preferably contains an aqueous medium. The main component of the aqueous medium is preferably water, but in addition to water, a water-soluble organic solvent can be used. Specifically, depending on the printing conditions (speed, plate depth, design, drying temperature), an alcohol-based organic solvent, a glycol-based organic solvent, etc. can be contained. The content of the aqueous medium is preferably 30% by mass or less based on the total amount of the overcoat agent. In the present invention, the term "mainly water" means that the content of water is the largest in the aqueous medium, and the term "water-soluble organic solvent" means that the solvent is liquid at 25°C and does not undergo phase separation when mixed with water at 25°C in a 1:1 ratio.
[0044] Examples of the alcohol-based organic solvent include methanol, ethanol, propanol, isopropanol, isobutanol, normal butanol, tertiary butanol, hexanol, octanol, and decanol.
[0045] Examples of the glycol-based organic solvent include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. These may be used alone or in combination of two or more.
[0046] <Method of manufacturing the overcoat agent> The overcoat agent can be obtained by feeding a resin solution, in which a resin is dissolved or dispersed in an organic solvent, and a solvent into an agitator equipped with an agitating blade, a rotor, etc., and mixing and stirring the solvent. There is no particular restriction on the stirring speed, and stirring can be performed at 50 to 2000 rpm. In order to improve the handling and coating properties of the overcoat agent, a solvent can also be appropriately added. The viscosity of the overcoat agent is preferably 50 to 300 mPa·s at 25° C. from the viewpoint of printability and the like.
[0047] <Formation of surface protective layer> The surface protective layer can be formed, for example, by printing an overcoat agent on a printed layer of a laminate in which a printed layer is provided on a substrate, and then removing the volatile components. The printing method includes a flexographic printing method, in which, for example, the overcoat agent is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture and applied. Thereafter, the coating is fixed by drying in an oven or the like to obtain a surface protective layer.
[0048] [Print layer] The printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin. When the printing layer contains the styrene-acrylic copolymer resin (B) and / or the styrene-maleic acid copolymer resin of the present invention, the water friction resistance, releasability, puncture resistance, and folding resistance of the packaging material become good. The styrene-acrylic copolymer resin (B) may be the same as the above-mentioned styrene-acrylic copolymer resin (A). In the printing layer, the total solid content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 10 to 70 mass %, more preferably 30 to 50 mass %, of the total solid content of the printing layer. When the total mass content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is within the above range, it is possible to achieve both toughness and flexibility, and therefore the releasability, puncture resistance, and folding resistance become good. The content ratio of the structure derived from a styrene monomer in 100% by mass of the printed layer is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20 to 70% by mass.
[0049] The total solid content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 50 mass% or more, more preferably 70 mass% or more, and particularly preferably 90 mass% or more, of the total solid mass of the resins contained in the printing layer.
[0050] The styrene-acrylic copolymer resin (B) and / or the styrene-maleic acid copolymer resin preferably have an acidic group, and when they have an acidic group, the acidic group is preferably neutralized with a basic compound. Examples of the acidic group include a hydroxyl group, an aldehyde group, a carbonyl group, a carboxyl group, and the like, and the carboxyl group is preferred. Suitable examples of the basic compound include an amine compound and an alkali metal.
[0051] Examples of the amine compound include ammonia, alkylamines such as diethylamine, triethylamine, and ethylenediamine, and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine. Examples of the alkali metal include sodium hydroxide and potassium hydroxide. These may be used alone or in combination of two or more.
[0052] The printing layer preferably contains an aqueous resin. The aqueous resin refers to a resin that can be dissolved or dispersed in water, and includes water-soluble resin and aqueous emulsion resin. Here, the water-soluble resin is a resin that is soluble in water, and the aqueous emulsion resin refers to a resin that is insoluble or poorly soluble in water, but is dispersed and stabilized in water using a surfactant or the like. The aqueous resin may be the above-mentioned styrene-acrylic copolymer resin (B) and / or styrene-maleic acid copolymer resin.
[0053] When the printed layer contains an aqueous emulsion resin, the average particle size of the aqueous emulsion resin is preferably 10 to 500 nm, and more preferably 30 to 200 nm. When a printing ink is used to form the printed layer, the average particle size is the average particle size in the printing ink.
[0054] The average particle size can be obtained, for example, by measuring with a particle size distribution measuring device (Microtrack MT-3000EX(II) manufactured by Microtrack Bell Co., Ltd.) using water as a dispersion medium by laser diffraction / scattering method.
[0055] The printed layer preferably contains both a water-soluble resin and an aqueous emulsion resin. The solid content mass ratio of the water-soluble resin and the aqueous emulsion resin is preferably water-soluble resin:aqueous emulsion resin=1:99 to 75:25, more preferably 1:99 to 55:45, and particularly preferably 15:85 to 35:65. When the solid content mass ratio of the water-soluble resin and the aqueous emulsion resin is within the above range, the balance between the water resistance and toughness of the printed layer is good, and the packaging material has good water friction resistance, releasability, puncture resistance, and folding resistance.
[0056] The thickness of the printed layer is preferably 0.1 to 10 μm, more preferably 0.3 to 6 μm, and particularly preferably 0.5 to 3 μm. In the present invention, not only a single printed layer but also a layer in which multiple printed layers are overlapped is regarded as the printed layer, and printed layers with different hues can be arbitrarily combined.
[0057] (Styrene-acrylic copolymer resin (B)) The styrene-acrylic copolymer resin (B) may be a water-soluble styrene-acrylic copolymer resin (b1) used as a water-soluble resin, or a styrene-acrylic copolymer resin emulsion (b2) used as an aqueous emulsion resin.
[0058] (Water-soluble styrene-acrylic copolymer resin (b1)) The water-soluble styrene-acrylic copolymer resin (b1) preferably has an acidic group, and in that case, the acid value is preferably 150 to 350 mgKOH / g, more preferably 200 to 300 mgKOH / g. When the water-soluble styrene-acrylic copolymer resin (b1) has an acidic group and the acid value is within the above range, the releasability and heat resistance of the packaging material are good.
[0059] The weight average molecular weight of the water-soluble styrene-acrylic copolymer resin (b1) is preferably 1,500 to 50,000, more preferably 1,500 to 30,000, and particularly preferably 1,500 to 8,000.
[0060] The water-soluble styrene-acrylic copolymer resin (b1) has a glass transition temperature of preferably 40 to 130°C, more preferably 60 to 100°C.
[0061] When the weight average molecular weight and glass transition temperature of the water-soluble styrene-acrylic copolymer resin (b1) are within the above ranges, the packaging material has good releasability, puncture resistance, and folding resistance.
[0062] The water-soluble styrene-acrylic copolymer resin (b1) may be a commercially available product, for example, GL-2439 or YL-1098 manufactured by Seiko PMC Corporation.
[0063] (Styrene-acrylic copolymer resin emulsion (b2)) The styrene-acrylic copolymer resin emulsion (b2) preferably has an acidic group, and in that case, the acid value is preferably 5 to 80 mgKOH / g, more preferably 20 to 60 mgKOH / g. When the styrene-acrylic copolymer resin emulsion (b2) has an acidic group and the acid value is within the above range, the water friction resistance and heat resistance of the packaging material are good.
[0064] The weight average molecular weight of the styrene-acrylic copolymer resin emulsion (b2) is preferably 2,000 to 600,000, and more preferably 10,000 to 600,000.
[0065] The glass transition temperature of the styrene-acrylic copolymer resin emulsion (b2) is preferably from -20 to 60°C, more preferably from 0 to 40°C.
[0066] When the weight average molecular weight and the glass transition temperature of the styrene-acrylic copolymer resin emulsion (b2) are within the above ranges, the packaging material has good releasability, folding resistance and puncture resistance.
[0067] As the styrene-acrylic copolymer resin emulsion (b2), a commercially available product may be used, and examples thereof include JONCRYL 662, 669, 668, 665, 667, PDX 7198, 633-E, LMV7051, 90, and HPD396 manufactured by BASF.
[0068] (Styrene-maleic acid copolymer resin) The styrene-maleic acid copolymer resin is preferably used as a water-soluble resin. The styrene-maleic acid copolymer resin preferably has an acidic group, and in this case, the acid value is preferably 100 to 180 mgKOH / g, and more preferably 120 to 160 mgKOH / g. When the styrene-maleic acid copolymer resin has an acidic group and the acid value is within the above range, the water friction resistance and heat resistance of the packaging material are good.
[0069] The weight average molecular weight of the styrene-maleic acid copolymer resin is preferably 1,500 to 50,000, and more preferably 4,000 to 30,000.
[0070] The glass transition temperature of the styrene-maleic acid copolymer resin is preferably from 40 to 120°C, more preferably from 60 to 100°C.
[0071] When the weight average molecular weight and glass transition temperature of the styrene-maleic acid copolymer resin are within the above ranges, the packaging material has good water abrasion resistance, puncture resistance, and folding resistance.
[0072] As the styrene-maleic acid copolymer resin, commercially available products may be used, for example, M-30 manufactured by Seiko PMC Corporation and Alastar series manufactured by Arakawa Chemical Industries, Ltd. can be used.
[0073] <Other resins contained in the printing layer> The printing layer may further contain other resins, such as acrylic resins, urethane resins, polylactic acid resins, polyamide resins, vinyl chloride-acrylic copolymer resins, castor oil resins, rosin resins, vinyl acetate resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, styrene-allyl alcohol copolymer resins, rosin-modified maleic acid resins, dammar resins, and modified resins thereof.
[0074] <Colorant contained in the printing layer> The printed layer preferably contains a colorant, and the content of the colorant is preferably 1 to 60% by mass, and more preferably 30 to 50% by mass, based on the total mass of the solid content of the printed layer.
[0075] The colorant is preferably a pigment, and either an organic pigment or an inorganic pigment can be used. As the organic pigment, it is preferable to use a pigment made of an organic compound and / or an organic metal complex. As the inorganic pigment, it is preferable to use one containing titanium oxide.
[0076] Specific examples of organic pigments are shown by their Colour Index International (CI) numbers. Preferably, CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 64, CI Pigment Orange 38, CI Pigment Orange 34, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, CI Pigment Red 178, CI Pigment Red 149, CI Pigment Red 144, CI Pigment Red 166, CI Pigment Violet 23, CI Pigment Violet 37, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 15:6, CI Pigment Green 7, CI Pigment Orange 34, CI Pigment Orange 64, and CI Pigment Black 7. These may be used alone or in combination of two or more.
[0077] (Inorganic pigments) Examples of inorganic pigments include titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, titanium oxide, and zinc oxide. Aluminum can be either leafing or non-leafing type, with the non-leafing type being preferred.
[0078] Titanium oxide Titanium oxide may be used in any of the crystal structures of anatase, rutile, and brookite. Among them, rutile titanium oxide is preferred because of its good pigment dispersibility. In industrial production of titanium oxide, rutile ore or ilmenite ore (FeTiO3) is used as the raw material. There are two main manufacturing methods: the chlorine method and the sulfuric acid method, and either method may be used. In addition, in order to improve printability in flexographic printing, it is preferable that the titanium oxide is surface-treated, and in particular, that the titanium oxide is surface-treated with at least one metal selected from the group consisting of Si, Al, Zn, Zr, and oxides thereof.
[0079] The titanium oxide preferably has an oil absorption of 14 to 35 ml / 100 g, more preferably 17 to 32 ml / 100 g, as measured by the method specified in JIS K5101. The titanium oxide preferably has an average particle size (median particle size) of 0.2 to 0.3 μm, as measured by a transmission electron microscope. The total content of the titanium oxide is preferably 1 to 60% by mass, more preferably 10 to 45% by mass, in 100% by mass of the printing ink. Multiple types of titanium oxide may be used in combination.
[0080] <Additives contained in the printing layer> The printing layer of the present invention may contain various additives as required, such as dispersants, waxes, extender pigments, leveling agents, antifoaming agents, and film-forming assistants. Specifically, various additives can be added, such as dispersions of wax resin particles such as polyethylene wax to improve abrasion resistance; extender pigments such as calcium carbonate, kaolin, barium sulfate, aluminum hydroxide, clay, and talc to improve drying properties and coating film hiding properties; inorganic particles and adhesive resins (acrylic resin, vinyl acetate resin) to impart anti-slip properties; leveling agents to improve leveling properties; antifoaming agents to impart antifoaming properties; basic compounds such as sodium hydroxide and potassium hydroxide to impart resolubility; and film-forming aids.
[0081] <Printing ink> The printed layer is preferably formed from a printing ink containing the above-mentioned colorant and the above-mentioned binder resin.
[0082] <Printing ink manufacturing method> The printing ink used to form the printing layer can be produced, for example, by dispersing a pigment in an organic solvent with a resin or the like using a disperser, and mixing the resulting pigment dispersion with a resin, various additives, an organic solvent, and the like. As the disperser, a commonly used one, for example, a roller mill, a ball mill, a pebble mill, an attritor, or a sand mill, can be used. The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the disperser, the filling rate of the grinding media, the dispersion processing time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, and the like. The viscosity of the printing ink at 25°C is preferably in the range of 50 mPa·s or more from the viewpoint of preventing the pigment from settling and dispersing appropriately, and 300 mPa·s or less from the viewpoint of workability efficiency during ink production and printing. For example, the method described in JP-A-2018-158986 can be used as the method for producing the printing ink.
[0083] <Formation of printing layer> The printing layer can be formed, for example, by printing with a printing ink on the paper substrate surface opposite to the heat seal layer, and then removing the volatile components. A suitable printing method is flexographic printing, in which, for example, the ink is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture, and applied. The printing layer can then be obtained by fixing the coating by drying in an oven or the like.
[0084] [Heat seal layer] The heat seal layer in the present invention is located on the paper substrate opposite to the surface having the printing layer. The heat seal layer of the packaging material improves heat sealability and folding resistance. The heat seal layer preferably contains at least one selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer. The resin contained in the heat seal layer may contain urethane resin, polyethylene resin, polypropylene resin, etc., in addition to ethylene-vinyl acetate copolymer resin, acrylic resin, and ethylene-based ionomer. These may be used alone or in combination of two or more.
[0085] <Ethylene-vinyl acetate copolymer resin> The ethylene-vinyl acetate copolymer resin is a copolymer made of ethylene and vinyl acetate. The vinyl acetate content in the ethylene-vinyl acetate copolymer resin is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 30 mass%, based on 100 mass% of the ethylene-vinyl acetate copolymer resin. The minimum film-forming temperature of the ethylene-vinyl acetate copolymer resin is preferably 40 to 120°C, more preferably 60 to 100°C. When the vinyl acetate content and the minimum film-forming temperature are within the above ranges, the heat sealability is good. The glass transition temperature of the ethylene-vinyl acetate copolymer resin is preferably -60 to 20°C, more preferably -25 to 5°C.
[0086] Examples of the ethylene-vinyl acetate copolymer resin that can be used include Aquatex EC series manufactured by Japan Coating Resins Co., Ltd. and Sumikaflex S-201HQ, S-305, S-305HQ, S-400HQ, S-401HQ, S-408HQE, S-450HQ, S-455HQ, S-456HQ, S-460HQ, S-467HQ, S-470HQ, S-480HQ, S-510HQ, S-520HQ, S-752, and S-755 manufactured by Sumitomo Chemical Co., Ltd.
[0087] <Acrylic resin> The acrylic resin is a resin containing a structural unit derived from an acrylic monomer. The acrylic resin preferably has a carboxy group or other acidic group. The acid value of the acrylic resin is preferably 20 to 120 mgKOH / g, more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. When the acid value of the acrylic resin is 20 mgKOH / g or more, the recyclability is good, and when it is 120 mgKOH / g or less, the blocking resistance is good. The glass transition temperature of the acrylic resin is preferably -40 to 90°C, more preferably -30 to 70°C, and particularly preferably -20 to 50°C. When the glass transition temperature of the acrylic resin is in the above range, the blocking resistance and heat sealability are good. In addition, the acrylic resin may preferably be a homopolymer of an acrylic monomer, a copolymer of an acrylic monomer and an acidic monomer, or a copolymer of ethylene and an acrylic monomer.
[0088] Examples of the monomer having an unsaturated double bond including the (meth)acrylic monomer include alkyl ester compounds of (meth)acrylic acid such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid amide derivatives containing at least one N-substituted methylol group, such as N-methylol (meth)acrylamide; Aminoalkyl esters of (meth)acrylic acid such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dipropylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, and dipropylaminopropyl (meth)acrylate; Mono- or diesters of (meth)acrylic acid of glycols such as diethylene glycol and dipropylene glycol, Styrene, α-methylstyrene and other styrene derivatives, Hydroxyalkyl ester compounds of (meth)acrylic acid, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate; Vinyl compounds having an acidic group, such as acrylic acid, methacrylic acid, maleic acid, and itaconic acid; Examples include: From the viewpoint of heat sealability, the acrylic resin preferably has a carboxy group and / or a hydroxyl group, and when the acrylic resin has a hydroxyl group, it preferably contains a hydroxyalkyl ester compound of (meth)acrylic acid as a monomer constituting the acrylic resin.
[0089] The acrylic resin may be a commercially available product, for example, JONCRYL PDX7356, PDX-7326, PDX-7430 manufactured by BASF, PE-1126, JE-1113, KE1148 manufactured by Seiko PMC Corporation, etc.
[0090] <Ethylene-based ionomer> Ethylene-based ionomer is a general term for resins in which the molecules of copolymers of ethylene and (meth)acrylic acid are intermolecularly bonded by metal ions. For example, metal salts of ethylene-methacrylic acid copolymers, metal salts of ethylene-acrylic copolymers, metal salts of ethylene-urethane copolymers, metal salts of ethylene-fluorine polymers, etc. are all called ethylene-based ionomers. Examples of metal ions that form salts include alkali metal ions and alkaline earth metal ions, specifically, sodium, potassium, calcium, magnesium, and zinc ions. The minimum film-forming temperature of ethylene-based ionomer resins is preferably 20 to 100°C, more preferably 40 to 80°C. When the minimum film-forming temperature is within the above range, the heat sealability is good.
[0091] As the ethylene-based ionomer, for example, Chemipearl S100, S111, S120, S650, S200, S300, S420, and S500 manufactured by Mitsui Chemicals can be used.
[0092] <Formation of heat seal layer> The heat seal layer can be formed, for example, by printing the heat seal agent on the paper substrate surface opposite to the surface protective layer, and then drying and removing the volatile components. As the printing method, gravure printing and flexographic printing are suitable. For example, in gravure printing, the agent is diluted with a diluting solvent to an appropriate viscosity and concentration as necessary, and is supplied to each printing unit alone or in a mixture, and then applied, and the coating is fixed by drying in an oven to obtain a heat seal layer. The resin content of the heat seal layer is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, based on 100% by mass of the heat seal layer. When the resin content of the heat seal layer is within the above range, the heat sealability is good. The thickness of the heat seal layer is preferably 0.1 to 10 μm, more preferably 2 to 7 μm. When the thickness of the heat seal layer is within the above range, the heat sealability and bending resistance tend to be improved.
[0093] [Paper base layer] The paper substrate layer is not particularly limited, and known ones can be used, for example, nonwoven fabric, medium-quality paper, wood-free paper, newsprint, Yupo paper, various coated papers, lining paper, impregnated paper, cardboard, art paper, cast paper, one-sided glossy kraft paper, bleached kraft paper, unbleached kraft paper, coated board, ivory paper, card paper, cup base paper, cast paper, light-shielding paper, and surface-treated paper substrates thereof can be mentioned. In addition, the paper substrate can also be a deposition paper substrate in which an inorganic compound such as silica, alumina, or aluminum is deposited on the paper substrate, and an anchor layer may be used to uniformly form the deposition layer on the paper substrate, and the deposition layer may further be coated with polyvinyl alcohol or the like. Furthermore, a paper substrate in which a heat-sealable resin such as polyethylene is formed on the deposition layer may be used. In addition, various melamine papers in which the paper substrate is impregnated with melamine resin can be used. Among the above, one-sided glossy kraft paper, bleached kraft paper, unbleached kraft paper, and non-coated paper without a coating layer such as a deposition layer are preferable. The paper base material has an average basis weight of 55 to 300 g / m 2 55-200g / m 2 More preferably, the thickness is 60 to 150 g / m 2 More preferably, the thickness is 60 to 120 g / m 2 When the average basis weight of the paper base material is within the above range, the water abrasion resistance, heat resistance, releasability, heat sealability, puncture resistance, and folding resistance are improved.
[0094] [Barrier layer] The packaging material of the present invention preferably has a barrier layer. The barrier layer improves the water vapor barrier property and also improves the gloss value. In particular, when the barrier layer is in contact with a paper substrate, the barrier layer fills the gaps in the paper substrate, thereby reducing the light transmittance of the entire packaging material and tending to improve the gloss value. In addition, when the barrier layer is located between the paper substrate and the printing layer, or between the paper substrate and the surface protective layer, the barrier layer tends to improve the gloss value by improving the smoothness of the printing layer and / or the surface protective layer. When the packaging material has a barrier layer, the barrier layer is preferably located between the paper substrate and the heat seal layer, and an inorganic compound layer can be formed on the paper substrate by a known method such as a vacuum deposition method or a sputtering method. Alternatively, an aluminum layer can be formed as a barrier layer by laminating an aluminum foil on the paper substrate by a dry lamination method or an extrusion lamination method. The thickness of the barrier layer is preferably 0.1 to 30 μm, more preferably 1 to 20 μm, and even more preferably 5 to 15 μm.
[0095] The barrier layer preferably contains an inorganic compound, and examples of the inorganic compound include, but are not limited to, aluminum, alumina, silica, etc. The purity of the inorganic compound is preferably 99% or more, and more preferably 99.9% or more.
[0096] <Vacuum deposition method> The vacuum deposition method is a method of depositing a metal such as aluminum by high-frequency induction heating, direct current heating, or electron beam heating at 1200 to 1500°C for 10 -1 ~10 -2 This method involves vapor deposition under conditions of about Pa. Prior to vacuum deposition, the object to be deposited may be subjected to a treatment for improving adhesion, such as a corona discharge treatment, on the surface. From the viewpoints of barrier properties, light blocking properties, and economic efficiency, the thickness of the metal film formed by vacuum deposition is preferably 10 to 300 nm.
[0097] <Sputtering method> The sputtering method is 10 -1 ~10 -2 The deposition is carried out by introducing an inert gas such as Ar and applying a voltage under conditions of about Pa. The thickness of the metal film formed is preferably 10 to 300 nm from the viewpoints of barrier properties, light-shielding properties, and economic efficiency.
[0098] [Adhesive layer] The packaging material of the present invention preferably has an adhesive layer. The adhesive layer can be formed by applying the following adhesive. As the adhesive, a two-liquid reactive adhesive, an acrylic adhesive, an anchor coating agent, a meltable polyolefin resin, etc. are preferably used, but are not limited to these. Among them, it is preferable to form the adhesive layer by a dry lamination method using a two-liquid reactive adhesive, or an extrusion lamination method using an anchor coating agent and a meltable polyolefin resin.
[0099] <Dry lamination method> The dry lamination method is a method of applying a two-liquid reactive adhesive consisting of polyol and polyisocyanate, which is diluted with an organic solvent to an appropriate viscosity, applied to the printed surface of the obtained printed matter, dried, and laminated by pressing with a sealant. Examples of such adhesives include TM-250HV / CAT-RT86L-60, TM-550 / CAT-RT37, and TM-314 / CAT-14B manufactured by Toyo-Morton Co., Ltd.
[0100] <Extrusion lamination method> The extrusion lamination method is a method in which meltable polyolefin resin is extruded into a film form from a slit-shaped device called a T-die, laminated on a substrate, and then bonded to another substrate. In the case of printed matter, an anchor coating agent is often applied to the printed layer before extrusion lamination. Meltable polyolefin resin can also be extruded onto the printed surface of a printed matter and a sealant can be bonded at the same time. As anchor coating agents, imine-based, butadiene-based, and isocyanate-based anchor coating agents can be used. Specific examples include EL-420 (imine-based), EL-452 (butadiene-based), EL-530A / B (isocyanate-based), and EL-540 / CAT-RT32 (isocyanate-based) manufactured by Toyo-Morton Co., Ltd. Meltable polyolefin resins include low-density polyethylene, polypropylene, and ethylene-vinyl acetate copolymers. Specific examples include Novatec LD LC600A (low-density polyethylene) manufactured by Japan Polyethylene Co., Ltd.
[0101] [Anchor coat layer] The packaging material of the present invention preferably has an anchor coat layer. When the packaging material has an anchor coat layer, the anchor coat layer is preferably located between the paper base layer and the heat seal layer, and can be formed by a known method such as gravure printing or flexographic printing. When the anchor coat layer is in contact with the paper substrate, the anchor coat layer fills the gaps in the paper substrate, which tends to reduce the light transmittance of the entire packaging material and improve the gloss value.
[0102] The anchor coat layer preferably contains an acrylic resin, and the acrylic resin is preferably an acrylic resin emulsion, and more preferably a styrene-acrylic copolymer resin emulsion.
[0103] <Preferable form for achieving gloss value of surface protective layer> As a preferred embodiment for achieving the gloss value of the surface protective layer, the thickness of the surface protective layer is preferably 0.3 to 10 μm, the content of the styrene-acrylic copolymer resin (A) is preferably 50 mass% or more of the total mass of the surface protective layer, the styrene-acrylic copolymer resin (A) preferably has an acidic group, in which case the acid value is preferably 20 to 200 mgKOH / g, and the content of a styrene monomer-derived structure in 100 mass% of the surface protective layer is preferably 5 mass% or more. In addition, the film thickness of the printed layer is preferably 0.1 to 10 μm, the content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 10 to 70 mass% of the total mass of the resin contained in the printed layer, and the content ratio of the styrene monomer-derived structure in 100 mass% of the printed layer is preferably 5 mass% or more. Furthermore, the basis weight of the paper base material is 55 to 300 g / m 2 It is preferable that: The gloss value tends to improve as the thickness of each layer, the content ratio of the styrene monomer-derived structure in each layer, and the basis weight of the paper base material increase. Furthermore, the higher the basis weight of the paper base material, the fewer the voids in the paper fibers, the more the ink penetration is suppressed, and the smoothness of the printing layer and the surface protective layer improves, so the gloss value also tends to improve. By adjusting the combination of the above-mentioned conditions that are effective for the gloss value and by adjusting each condition, the desired gloss value can be achieved.
[0104] <Manufacturing method of packaging materials> The present invention relates to a method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the method including the steps of printing a printing ink on one side of the paper base material to form a printing layer, printing an overcoat agent containing a styrene-acrylic copolymer resin (A) on the printing layer to form a surface protective layer, and applying a heat seal agent to the other side of the paper base material to form a heat seal layer. The order of the steps does not matter, but it is preferable to form the printing layer, the surface protective layer, and the heat seal layer in this order.
[0105] The manufacturing method of the packaging material will be described by taking a configuration of a heat seal layer / barrier layer / adhesive resin layer / paper base material layer / printing layer / surface protection layer as an example. However, the configuration of the packaging material in the present invention is not limited to the above.
[0106] As an example of the manufacturing method, first, a paper base material (unbleached kraft paper: kraft paper using unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., unglazed kraft K, basis weight 70 g / m) 2 ) and apply dry lamination adhesive TM-250HV / CAT-RT86L-60 at a rate of 4g / m 2Then, aluminum foil is laminated to form a barrier layer. A heat seal agent containing an ethylene-vinyl acetate copolymer resin, an acrylic resin, or the like is applied onto the barrier layer to form a heat seal layer. Thereafter, a printing ink is printed on the side of the paper substrate that does not have the barrier layer to form a printed layer, and an overcoat agent is printed to form a surface protective layer, thereby producing a packaging material having a configuration of heat seal layer / barrier layer / adhesive resin layer / paper substrate layer / printed layer / surface protective layer.
[0107] [Packaging bag] The packaging material in the present invention is cut to a predetermined size, and the edges are heat-sealed in a state where the heat-sealable layers are joined together to form a packaging bag. The heat-sealing temperature is preferably 50 to 250°C, and more preferably 80 to 180°C. The heat-sealing pressure is 1 to 5 kg / cm. 2 The conditions are as follows. One sheet of packaging material may be folded and the edges may be heat sealed, or two or more sheets of packaging material may be heat sealed. Also, the packaging bag may be one in which all openings are heat sealed after the contents are packed. This packaging bag can be widely used as a packaging bag for food, medicine, etc. In particular, it is preferably used as a secondary packaging material. Secondary packaging material refers to a packaging material for further packaging already packaged food, medicine, etc. Since the secondary packaging material is often located in the outermost layer of the package, the secondary packaging material frequently comes into contact with other objects, and furthermore, the secondary packaging material may be damaged by external forces. Therefore, it is preferable to use the packaging material of the present invention, which has excellent resistance to various types of resistance such as water friction resistance, heat resistance, puncture resistance, and bending resistance. EXAMPLES
[0108] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted. In addition, "NV." represents the mass % of non-volatile content.
[0109] <Preparation Example 1> (Preparation of urethane resin solution PU1) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 227.0 parts of polyester polyol, which is a condensate of adipic acid and 3-methyl-1,5-pentanediol, 9.6 parts of PEG (polyethylene glycol having a number average molecular weight of 2000), 30.1 parts of 2,2-dimethylolpropanoic acid (DMPA), and 250 parts of methyl ethyl ketone (MEK) were mixed while introducing nitrogen gas, and 90.6 parts of isophorone diisocyanate (IPDI) was dropped over 1 hour while stirring, and the mixture was reacted at 80°C for 4 hours to form a terminal isocyanate prepolymer, and a terminal isocyanate prepolymer solution was obtained. After cooling the obtained terminal isocyanate prepolymer solution to room temperature, a mixture of 2.7 parts of 2-aminoethylethanolamine (AEA) and 150 parts of isopropanol (IPA) was gradually added to the terminal isocyanate prepolymer solution at room temperature under stirring, and then reacted at 40 ° C for 2 hours to obtain a solvent-based polyurethane resin solution. Next, 38.1 parts of 10% ammonia water and 801.4 parts of ion-exchanged water were gradually added to the solvent-based polyurethane resin solution to neutralize it and make it water-soluble, and then 0.5 parts of an antifoaming agent was added to distill off MEK and IPA under reduced pressure, and water was added to adjust the solid content, obtaining a urethane resin solution PU1 with a solid content of 28% and a weight average molecular weight of 38,000.
[0110] <Production Example 1> (Production of printing ink K1) A mixture of 25.9 parts of water, 18 parts of Pigment Black 7, 5 parts of urea, and 15 parts of styrene-acrylic copolymer resin (B) solution SAC1 (acid value: 213 mg KOH / g, weight average molecular weight: 8000, glass transition temperature: 73°C, solid content: 28%, content of styrene monomer derived structure: 30 mass%) was kneaded and dispersed using a bead mill, and then 32.7 parts of styrene-acrylic copolymer resin (B) emulsion SAC2 (hydroxyl value: 36 mg KOH / g, glass transition temperature: 14°C, solid content: 40%, content of styrene monomer derived structure: 32 mass%) and 3 parts of polyethylene wax were added and stirred to obtain printing ink K1.
[0111] <Production Examples 2 to 9, Comparative Production Examples 1 and 2> (Production of Printing Inks K2 to K11) Printing inks K2 to K11 were obtained in the same manner as in Production Example 1, except that the raw materials and compounding ratios shown in Table 1-1 were used. The properties of the raw materials used are as follows. Styrene-maleic acid copolymer resin solution SMA1 (X-228L manufactured by Seiko PMC, acid value: 140 mg KOH / g, glass transition temperature: 83°C, solid content: 28%, content of styrene monomer-derived structure: 25% by mass) Acrylic resin solution AC1 (AW-36H, manufactured by Seiko PMC, acid value: 62 mg KOH / g, glass transition temperature: 53°C, solid content: 28%) Urethane resin emulsion PU2 (Taisei Fine Chemical Co., Ltd. WBR016U, acid value: 7 mg KOH / g, solid content: 40%) Acrylic resin emulsion AC2 (acid value: 215 mg KOH / g, weight average molecular weight: 8500, glass transition temperature: 85°C, solid content: 40%)
[0112] [Table 1-1]
[0113] <Production Example 10> (Production of Overcoat Agent V1) 4.3 parts of water, 87.6 parts of styrene-acrylic copolymer resin (A) emulsion SAC3 (acid value 100 mg KOH / g, glass transition temperature: 16°C, solids content 40%, content of styrene monomer derived structure 31% by mass), and 8.1 parts of polyethylene wax were added and mixed by stirring to obtain overcoat agent V1.
[0114] <Production Examples 11 to 14, Comparative Production Examples 3 to 4> (Production of Overcoat Agents V2 to V7) Overcoat agents V2 to V7 were obtained in the same manner as in Production Example, except that the raw materials and compounding ratios shown in Table 1-2 were used. The properties of the raw materials used are as follows. Styrene-acrylic copolymer resin emulsion SAC4 (acid value: 40 mgKOH / g, glass transition temperature: 49°C, solid content: 40%, content of styrene monomer-derived structure: 30% by mass) Styrene-acrylic copolymer resin emulsion SAC5 (acid value: 45 mgKOH / g, glass transition temperature: 22°C, solid content: 40%, content of styrene monomer-derived structure: 33% by mass) Styrene-acrylic copolymer resin emulsion SAC6 (acid value: 200 mg KOH / g, glass transition temperature: 123°C, solid content: 40%, content of styrene monomer-derived structure: 31% by mass)
[0115] [Table 1-2]
[0116] Example 1 (Production of Laminate P1) Next, unbleached kraft paper: kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., unbleached kraft K, basis weight 100 g / m 2 ) was printed with printing ink K1 at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200 W dryer to form a printed layer (thickness 2 μm). Overcoat agent V1 was printed on the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p1 having a paper substrate / printed layer / surface protective layer configuration. Aluminum foil (thickness 6 μm) was bonded to the side of the substrate opposite the printed layer in the intermediate laminate p1 by extrusion lamination under the following conditions: adhesive resin: polyethylene (melting point: 120°C), resin temperature: 330°C, coating speed: 80 m / min, coating thickness: 10 μm. Then, heat sealant H1 was printed on the aluminum foil using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm under the following conditions: printing speed: 50 m / min, in-line oven temperature: 70°C, to obtain a packaging material P1 having a configuration of heat seal layer / barrier layer / adhesive resin layer / paper substrate / printed layer / surface protection layer.
[0117] <Examples 2 to 21, 24 to 26, Comparative Examples 1 to 10> (Production of packaging materials P2 to 21, P24 to 26, and P'1 to 10) Packaging materials P2 to 21, P24 to 26, and P'1 to 10, each having the same configuration, were prepared using the same procedures as for preparing the above packaging materials, except that the printing inks, overcoat agents, heat seal agents, and paper base materials shown in Tables 2-1 to 2-3 and Table 3 were used.
[0118] The properties of the raw materials used are as follows: <Paper base material> Kraft paper (Nippon Paper Industries, double-glazed Kraft K, basis weight 50g / m 2 ) Kraft paper (Nippon Paper Industries, double glazed Kraft K, basis weight 60g / m 2 ) Kraft paper (Nippon Paper Industries, double glazed Kraft K, basis weight 100g / m 2 ) Kraft paper (Nippon Paper Industries, double-glazed Kraft K, basis weight 150g / m 2 ) Kraft paper (Nippon Paper Industries, double glazed Kraft K, basis weight 200g / m 2 ) Coated paper (Oji Materia, OK Ball, basis weight 270g / m 2 ) Coated paper (Oji Materia, OK Ball, basis weight 310g / m 2 ) <Heat sealant> H1: Heat sealant containing ethylene vinyl acetate copolymer resin (Japan Coating Resins, Aquatex MC3800, minimum film-forming temperature: 100°C, solid content 50% by mass) H2: Heat sealant containing acrylic resin (acid value 100 mgKOH / g, glass transition temperature 20°C, solid content 48% by mass) H3: Heat sealant containing ethylene acrylic copolymer resin (Japan Coating Resins, Aquatex AC3100, minimum film-forming temperature: 100°C, solid content 44.5% by mass) H4: Heat sealant containing ethylene ionomer (Mitsui Chemicals, Chemipearl S100, minimum film-forming temperature: 65°C, solid content 27% by mass)
[0119] <Example 22> (Production of packaging material P22) On the side of the intermediate laminate p1 opposite the printed layer of the substrate, an anchor coating agent ACC1 was printed using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm at a printing speed of 50 m / min and an in-line oven temperature of 70°C, and then a heat seal agent H1 was printed under the same conditions as above to obtain a packaging material P22 having a configuration of heat seal layer / anchor coat layer / paper substrate / printed layer / surface protection layer.
[0120] (Anchor Coat Agent ACC1) ACC1: Anchor coating agent containing styrene-acrylic copolymer resin emulsion (acid value 100 mgKOH / g, glass transition temperature 30°C, solid content 50% by mass)
[0121] <Example 23> (Production of packaging material P23) Aluminum-deposited paper (basis weight 200 g / m) with an aluminum layer as a barrier layer 2On the surface opposite to the aluminum vapor deposition surface of the paper, a printing ink K1 was printed at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200 W dryer to form a printed layer (thickness 2 μm). On the printed layer, an overcoat agent V1 was printed at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p23 having a barrier layer / paper substrate / printed layer / surface protective layer configuration. A heat seal agent H1 was printed on the side opposite the printed layer of the substrate in the intermediate laminate p23 using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm at a printing speed of 50 m / min and an in-line oven temperature of 70°C to obtain a packaging material P23 having a configuration of heat seal layer / barrier layer / paper substrate / printed layer / surface protection layer.
[0122] [Evaluation of packaging materials] Details of the resulting packaging material are given below. The packaging materials P1-26 and P'1-10 obtained in Examples 1-26 and Comparative Examples 1-10 were evaluated as follows. The results are shown in Tables 2-1-3 and Table 3. The 60 degree gloss value of the surface protective layer was measured for the Examples and Comparative Examples other than Comparative Example 5, which had no surface protective layer, by the method described in JIS Z8741:1997.
[0123] <Water friction resistance> The obtained packaging material was cut into a size of 25 mm x 150 mm, and the water friction resistance of the surface protective layer was evaluated according to the following criteria using a Gakushin-type friction fastness tester manufactured by Tester Sangyo Co., Ltd. When there was no surface protective layer, the printed layer was evaluated in the same manner. AA, A, B, and C are ranges that do not pose any practical problems. Test conditions Load: 200g, number of reciprocations: 2, paper: 5 drops of water on Kanakin cloth Evaluation Criteria AA. The printed layer is not removed, there are no visible scratches on the surface of the printed layer, and the exposed area ratio of the base paper is 0%. A. The printed layer is not removed, there are slight visible scratches on the surface of the printed layer, and the exposed area ratio of the base paper is less than 1%. B. The paper has a small amount of ink on it. A small amount of the printing layer has been removed, and the exposed area of the base paper is between 1% and 10%. C. The paper has a thin layer of ink on the entire surface. The printed layer has been removed slightly, and the exposed area of the base paper is between 10% and 20%. D. The ink is thickly adhered to the entire surface of the paper. Most of the printing layer has been removed, and the exposed area of the base paper is 20% or more.
[0124] <Heat resistance> The obtained packaging material was cut to a size of 25 mm x 150 mm, and the glossy side of an aluminum foil (thickness: 15 μm) of a size of 25 mm x 150 mm was placed on the surface protective layer, and heat-sealed using the following device and conditions, and the heat resistance was evaluated based on the state of the printed layer when the aluminum foil was peeled off according to the following criteria. When there was no surface protective layer, the printed layer was evaluated in the same manner. A, B, and C are ranges that do not pose any practical problems. <Heat sealing conditions> Equipment: Thermal gradient heat sealer [Toyo Seiki Co., Ltd.; TYPE, HG-100], Seal width: 10mm from the bent part, heater temperature: 160℃, Sealing pressure: 2kg / cm 2 , Sealing time: 1sec Evaluation Criteria A. The printed layer is not removed and the exposed area of the base paper is less than 1%. B. The paper has a small amount of ink on it. A small amount of the printing layer has been removed, and the exposed area of the base paper is between 1% and 10%. C. The paper has a thin layer of ink on the entire surface. The printed layer has been removed slightly, and the exposed area of the base paper is between 10% and 20%. D. The ink is thickly adhered to the entire surface of the paper. Most of the printing layer has been removed, and the exposed area of the base paper is 20% or more.
[0125] <Releasability> The obtained packaging material was cut into two pieces of 40 mm square, and the heat seal layer and the surface protection layer of the cut packaging material were overlapped, and the heat seal layer was pressed at a temperature of 40°C and a load of 100 kg / cm using a small heat press machine H30-10D manufactured by AS ONE Corporation. 2 (meaning a significantly excessive load). After leaving it in that state for 12 hours, the two overlapping printed sheets were peeled off, the peeling state was visually observed, and evaluated according to the following criteria. When there was no surface protective layer, the heat seal layer and the printed layer were overlapped, and the evaluation was performed in the same manner. A, B, and C are ranges that do not pose any practical problems. Evaluation Criteria A. The amount of the printed layer transferred to the heat seal layer is less than 1% by area. B. The amount of the printed layer transferred to the heat seal layer is 1 area % or more and less than 10 area %. C. The amount of the printed layer transferred to the heat seal layer is 10% by area or more and less than 20% by area. D. The amount of the printed layer transferred to the heat seal layer is 20% or more by area.
[0126] <Heat sealability> The obtained packaging material was cut to a size of 15 mm wide x 100 mm long, folded longitudinally so that the heat-sealed layer surfaces overlapped each other, and heat-sealed using the following equipment and conditions. Both unsealed ends were fixed to a small tensile tester to evaluate the heat-seal strength. When the heat seal layer was not present, the film was folded in the longitudinal direction so that the barrier layer surfaces overlapped each other, and the evaluation was carried out in the same manner. A, B, and C are ranges that do not pose any practical problems. <Heat sealing conditions> Equipment: Heat seal tester manufactured by Tester Sangyo Co., Ltd. Seal width: 10mm from the bent part, heater temperature: 160℃, Sealing pressure: 2kg / cm 2 , Sealing time: 1sec <Heat seal strength measurement conditions> Equipment: Intesco small tensile testing machine (model: IM-20), test piece width: 15 mm, Peeling mode: 90° peeling, tensile speed: 300mm / min Evaluation Criteria A. The heat seal strength is 5.0N or more. B. The heat seal strength is greater than or equal to 3.5N and less than 5.0N. C. The heat seal strength is 1.0N or more and less than 3.5N. D. The heat seal strength is less than 1.0 N.
[0127] <Puncture resistance> The obtained packaging material was cut into 70 mm squares, and tested under the following test conditions using a method in accordance with JIS1707, and evaluated according to the following criteria. A, B, and C are ranges that do not pose any practical problems. <Penetration test conditions> Piercing speed: 50mm / min, needle diameter: 1mm, Needle piercing surface: Surface protective layer surface, or if there is no surface protective layer, the printed layer surface Evaluation Criteria A. The puncture strength is 12N or more. B. The puncture strength is greater than or equal to 10N and less than 12N. C. The puncture strength is 5N or more and less than 10N. D. The puncture strength is less than 5N.
[0128] <Bending resistance> The obtained packaging material was folded 180° so that the heat seal layer was on the inside, and then folded 180° so that the surface protective layer was on the inside. The degree of cracking of the coating of the surface protective layer was then evaluated according to the following evaluation criteria. A, B, and C are ranges that do not pose any practical problems. A: No cracks B: Minor scratches C: Some cracks D: Many cracks
[0129] [Table 2-1]
[0130] [Table 2-2]
[0131] [Table 2-3]
[0132] [Table 3]
[0133] According to the present invention, a packaging material excellent in water friction resistance, heat resistance, releasability, heat sealability, puncture resistance, and folding resistance can be provided. On the other hand, Comparative Example 1, which does not have a heat seal layer, did not meet the standards in heat sealability and folding resistance. Comparative Example 2, which does not contain either styrene-acrylic copolymer resin (B) or styrene-maleic acid copolymer resin in the printing layer but contains acrylic resin, and Comparative Example 3, which does not contain either styrene-acrylic copolymer resin (B) or styrene-maleic acid copolymer resin but contains urethane resin, did not meet the standards in release property, puncture resistance, and folding resistance. Comparative Example 4, which does not contain a surface protective layer, did not meet the standards in water friction resistance, heat resistance, and puncture resistance. Comparative Example 5, which does not contain styrene-acrylic copolymer resin (A) but contains polyurethane resin in the surface protective layer, did not meet the standards in heat resistance, release property, and puncture resistance, and Comparative Example 6, which does not contain styrene-acrylic copolymer resin (A) but contains acrylic resin in the surface protective layer, did not meet the standards in heat resistance, release property, puncture resistance, and folding resistance. The basis weight of the paper base material is 55 g / m 2 In Comparative Example 7, the folding resistance was not satisfied, and the basis weight of the paper base material was less than 300 g / m 2 In Comparative Example 8, the releasability did not satisfy the criteria, and in Comparative Example 9 and Comparative Example 10, the gloss value of which did not satisfy the range of 5 to 45, did not satisfy the criteria for water abrasion resistance and folding resistance.
Claims
1. A packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the surface protective layer comprises a styrene-acrylic copolymer resin (A), the printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the surface protective layer has a 60 degree gloss value of 5 to 45 as measured by the method described in JIS Z8741:1997; The average basis weight of the paper base material is 55 to 300 g / m 2 That is, packaging materials.
2. The packaging material of claim 1 further comprising a barrier layer.
3. The packaging material according to claim 1 or 2, further comprising an anchor coat layer.
4. 3. The packaging material according to claim 1, wherein the surface protective layer has a 60 degree gloss value of 10 to 35 as measured by the method described in JIS Z8741:1997.
5. 3. The packaging material according to claim 1, wherein the heat seal layer has a thickness of 1 to 10 μm.
6. The packaging material according to claim 1 or 2, wherein the heat seal layer comprises an ethylene-vinyl acetate copolymer resin.
7. The packaging material according to claim 1 or 2, which is used as a secondary packaging material.
8. A packaging bag formed from the packaging material according to claim 1 or 2.
9. A method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, comprising: The average basis weight of the paper base material is 55 to 300 g / m 2 and Step 1: forming the printing layer by flexographically printing a printing ink containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin on one surface of the paper base material; A step 2 of flexographically printing an overcoat agent containing a styrene-acrylic copolymer resin (A) on the printed layer to form the surface protective layer having a 60 degree gloss value of 5 to 45 as measured by the method described in JIS Z8741:1997; and a step 3 of applying a heat seal agent to the other surface of the paper base material to form the heat seal layer.
Citation Information
Patent Citations
Packaging material
JP1995080989A
Coating material and its method for production, and decorative paper
JP2001192617A
Ptp packaging member
JP2003081336A
Aqueous pigment dispersion and aqueous printing ink composition comprising the same
JP2011122023A
Water-based gravure printing ink composition for carton
JP2013035967A